A model of leisure involvement, residential satisfaction, and place attachment in passive older migrants. (8th November 2022) - Jin, Wenmin; Yoon, Hyejin; Lee, Seoki
Abstract : Although the influence of mobility on place attachment has received attention in the literature, this relationship varies between groups. Unlike those who move to enjoy their retirement, for example, older migrants arriving in Shenzhen come to the city 'passively, ' drawn by the needs of their children. This paper advances understanding of the concept of place attachment by illustrating the relationships between its components. Analysis of interview and questionnaire responses revealed the following relationships between three focal components of place attachment. Place dependence first directly influenced affective attachment and then indirectly affected place identity. Leisure involvement had a positive impact on place dependence and affective attachment but no direct effect on place identity. Residential satisfaction was an antecedent of all three focal dimensions of place attachment. No direct relationship was found between leisure involvement and residential satisfaction.